Perlindungan Hukum Terhadap Para Pihak Dalam Perjanjian Kredit Sindikasi - Nicko Priady (Magister Kenotariatan, Universitas Jambi, 2021)
This study aims to identify and criticize the arrangements, procedures and positions of all parties involved in syndicated financing. The formulation of the problem that will be discussed in this article is about the legal relationship between the parties in a syndicated loan to resolve bad loans when they default, and the legal protection of the parties in a syndicated loan agreement. The type of research is normative law, which is a research method that emphasizes legislation, conceptual law, and case law, and describes theories related to research problems. The results show that the implementation of Syndicated Loans is related to the rights and obligations of the parties. As long as the parties fulfill this and carry out the agreed agreements and carry out supervision simultaneously, the risk of default will be smaller. The regulation regarding the authority and rights and obligations between the Debtor and the Bank in the Syndicated Credit Agreement must be clearly stated in the Syndicated Credit Agreement so that there is no gap in the norm of ambiguity that can cause problems in the future.